Ability of kaolin clays in Adsorption of Toluene 0-Nitro Toluene and 2,4-Dinitro Toluene Part 1 - Isha, S.A.; Hassan, S.A.; Jahsim, K.G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was concerned with the adsorption of Toluene ,0· nitro Toluene and 2,4.dinitro Toluene on The surface of kaolin clay. The adsorption isotherms were of types( S3,S4 ) according to Giles classification and were in a good correlation with Freundlich equation in the range of cuncenlraliuns studied. The re5ult indicated that adsorption capacity increase with the increase of equilibrium concentration. The effect of the nwnber of substituted nitro groups in the adsorption extent of toluene was found to decrease in the following order:· Toluene > 2,4-dinitro toluene > 0-nitro toluene Adsorption on kaolin surface were examined as afunction of temperature in the range (298·328K) .1he extent of adsorption was found to increase with the increase in temperature (Endothennic). Adsorption studies of Toluene on kaolin at different pH values showed the following sequence:- pH 4 > 11 > 7 While for O·nitro toluene and 2,4-dinitro toluene showed the following order:- pH 11 > 4> 7